Impactos das estratégias de comunicação em empresas globais um experimento no mercado automobilístico - Toledo, Marcelo Vergilio Paganini de (2013)
This study sought to assess whether the communication strategy of a global company affects consumer involvement with the product category sold by it , the image of their country of origin and its corporate reputation . An experiment was conducted to test the theoretical model and hypotheses using a sample of 407 individuals defined by judgment of the investigator. This sample was divided into an experimental group of 202 respondents and a control group of 205 people. The scales used in the experiment were validated as to their content , criterion and construct , to be satisfactory for use . The results showed that the proposed theoretical model is consistent and completed the research problem developed . All hypotheses were confirmed surveyed , which leads to the conclusion that there is evidence in this study that the communication strategy of a global company does not impact consumer involvement with the product category manufactured by it , to the image of his country source and its corporate reputation .